Reclaiming the Faravahar Zoroastrian Survival in Contemporary Tehran - Fozi, Navid (Iranian Studies Series, 2014)
Reclaiming the Faravahar is an ethnographic study of the contemporary Zoroastrians in Tehran. It examines many public discursive and ritual performances to show how they utilize national, religious, and ethnic categories to frame the Zoroastrian identity within the longstanding conflict between Iranian Shi'a and Arab Sunnis, defining and defending Zoroastrians' identity and values in Shi'i dominated Iran.